Enhanced in-vitro propagation of selected rangeland species for large-scale restoration - Louhaichi, Mounir; Imtinene, Hamdeni; Siebert, A. (CGIAR System Organization, 2024)
Incorporation of organic growth additives to enhance in vitro propagation of selected shrub/tree species for large scale restoration and for supporting local communities dependent on agrosilvopastoral systems in building resilience.